Analysis of urban form typology using urban heat island indicators: Case study of Ferdous neighborhood of Tabriz - Abdi, Zanyar; Alizadeh, Hooshmand; Mohammadi, Saleh; Sabouri, Saber (Frontiers in Ecology and Evolution, 2023)
Urbanization, with the acceleration of construction operations in cities, is the main reason for in-creasing the absorption of thermal energy in urban areas, which leads to climate change, especially urban form has responded differently depending on environmental dimension of urban context concerning the urban heat island intensity. In the last Studies, Researchers have not Codified the effect of urban form on heat islands in the form of a comprehensive model. It is necessary to examine each urban context according to its own conditions. Accordingly, this study aims to identify the effect of building form variability on reducing the intensity of heat islands in Ferdous context of Tabriz in the form of comprehensive modelling as a new task. Our conceptual framework was based on urban form typologies in microscale affect the amount of energy intake and consumption, especially the intensity of heat islands, and whether the use of desirable types can be responsive to reducing the intensity of these islands? In this regard, using a quantitative analysis method in Rhinoceros software, especially using Grasshopper plugins, urban form is investigated. This analysis includes both the coldest and hottest days of the year. The results show that the optimal model is the cross typology.